2019
DOI: 10.1177/1477153519872801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intensity of short-wavelength light on electroencephalogram and subjective alertness

Abstract: Short-wavelength light is known to have an effect on human alertness in the night-time. However, there are very few studies that focus on the effect of intensity of light on alertness. This study evaluates the acute alerting ability of short-wavelength light of three different intensities (40 lux, 80 lux and 160 lux). Eight subjects participated in a 60-minute exposure protocol for four evenings, during which electroencephalogram (EEG) as well as subjective sleepiness data were collected. EEG power in the beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…21,22 These are also indirect evidences that melatonin suppression is not necessary for us to observe an alerting effect of light. Secondly, in previous study, 16 only 160 lx blue light significantly increased alertness. 40 lx and 80 lx blue lights seemed to have an effect, though it is not statistically significant.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…21,22 These are also indirect evidences that melatonin suppression is not necessary for us to observe an alerting effect of light. Secondly, in previous study, 16 only 160 lx blue light significantly increased alertness. 40 lx and 80 lx blue lights seemed to have an effect, though it is not statistically significant.…”
Section: Discussionmentioning
confidence: 69%
“…Experiment protocol of this study is kept consistent with the previous study. 16 Each participant completed two sessions over two nights, starting at around the same time (8 p.m.). Participants were fitted with EEG electrodes prior to the start of the exposure.…”
Section: Experiments Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that the effective use of colours in the design of classrooms do have significant impacts on students’ perceptual performances. Interestingly, some studies carried out explored the intensity lighting impacts have on people’s electroencephalogram (EEG) power [ 15 , 16 ]. Results have demonstrated the stimulus of short and long wavelength light on people’s alpha, theta, and beta power, suggesting that coloured light can promote acute alertness and improve performance on tasks requiring sustained attention.…”
Section: Introductionmentioning
confidence: 99%